The insurrection of little selves the crisis of secular nationalism in India - Nigam, Aditya (New Delhi ; Oxford : Oxford University Press, 2006)
This book argues that in times of crises, Nehruvian secular-nationalism has shown itself to be fundamentally Hindu in its latent assumptions. Its quest for a national culture has led it to produce the dominant culture as the norm and so marginalise minority cultures.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Secularism -- India; Nationalism -- India; India -- Politics and government -- 1977-